ANALYSIS OF THE FACTORS DETERMINING FINANCIAL MANAGEMENT IN STUDENTS AT THE ECONOMICS FACULTY - Sari, Nita; Mardi; Fauzi, Achmad (Transpublika Publisher, 2022)
This research aims to determine the effect of lifestyle, self-control, and spiritual intelligence on the financial management of students in the Faculty of Economics, State University of Jakarta. The method used in this research is quantitative method. The population in this research is the students of the Faculty of Economic State University of Jakarta in the year 2018 with a total of 268 people. The sample used were as many 158 people using proportional random sampling techniques. The data collection method used is a survey method with a questionnaire. The data analysis techniques used are descriptive statistical analysis, multiple regression analysis test, normality test, linearity test, t test, F test, and coefficient of determination test. Tests from the analysis show that lifestyle, self-control, and spiritual intelligence partially and simultaneously have a positive and significant effect on financial management. This shows that the higher the level of lifestyle, self-control, and spiritual intelligence of students, the higher the level of financial management.